The Sectarian Ideology of the Islamic Online Media in Indonesia - Moch. Syarif Hidayatullah (Insaniyat : Journal of Islam and Humanities, 2017)
Numerous  Islamic  groups  in  Indonesia  use  the  internet  to  offer  ideology  against  other  groups  or other sects to internet users. This study focuses on sectarian ideology on Islamic online media in Indonesia. Having combined and sought this media, I found that lppimakassar.com and manhajsala- fi.com  are  the  most  intensive  sites  in  offering  sectarian  ideology.  This  study  aims  to  examine  the ideological identity and pattern of the websites linked to the administrators or writers of the web- sites. To find their ideology, this article uses topic headings, news, and articles to analyze. This meth- od has led me to find two Islamic online media: lppimakassar.com and manhajsalafi.com. The former is affiliated to the Salafi group while the latter to the Aswaja group. These two websites adopt their thoughts abroad.DOI: 10.15408/insaniyat.v1i2.5468